2007
DOI: 10.1590/s0100-879x2007000300016
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic activation in rats with L-NAME-induced hypertension

Abstract: We evaluated the hemodynamic pattern and the contribution of the sympathetic nervous system in conscious and anesthetized (1.4 g/kg urethane, iv) Wistar rats with L-NAME-induced hypertension (20 mg/ kg daily). The basal hemodynamic profile was similar for hypertensive animals, conscious (N = 12) or anesthetized (N = 12) treated with L-NAME for 2 or 7 days: increase of total peripheral resistance associated with a decrease of cardiac output (CO) compared to normotensive animals, conscious (N = 14) or anesthetiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
(13 reference statements)
4
11
0
1
Order By: Relevance
“…3), the correlations between HT and VT were similar in control, L -NAME- or propranolol-treated groups, with no clear positive or negative influence in both locations. This fits with the suggestion that the L -NAME-induced increase in blood pressure is mainly due to an increased peripheral resistance and not to an increased volume output [37]. In the kidney, L -NAME induced a positive correlation mainly between HT and RC, which also suggests an increased sympathetic activation, therefore leading to an increased renin secretion and thus contributing to the increase in peripheral resistance.…”
Section: Discussionsupporting
confidence: 88%
“…3), the correlations between HT and VT were similar in control, L -NAME- or propranolol-treated groups, with no clear positive or negative influence in both locations. This fits with the suggestion that the L -NAME-induced increase in blood pressure is mainly due to an increased peripheral resistance and not to an increased volume output [37]. In the kidney, L -NAME induced a positive correlation mainly between HT and RC, which also suggests an increased sympathetic activation, therefore leading to an increased renin secretion and thus contributing to the increase in peripheral resistance.…”
Section: Discussionsupporting
confidence: 88%
“…Although in rats, many authors have used administration of doses higher than 20 mg/kg/day (Santos de Araujo et al, 2013;Sung et al, 2013), in this study, 7-days treatment of rats at this dose was sufficient to induce a significant increase in blood pressure. These data are in agreement with those of Biancardi where significant increase of blood pressure was observed after 2 and 7 days L-NAME administration (Biancardi et al, 2007). Moreover the increased pressure induced by L-NAME in the present work was enough higher for at least 7additional days from the end of the hypertension induction protocol when compared with control group.…”
Section: Discussionsupporting
confidence: 93%
“…(68) The direct effect of L-NAME preventing endothelial synthesis of NO and reducing the tonic vasodilation is an important mechanism in the genesis of this model experimental hypertension. (69) The pressure in this experimental model was also associated with kidney damage, characterized by glomerulosclerosis, glomerular ischemia and renal interstitial infiltrate. (65,66) Studies from our group showed that 10 weeks of APT mildmoderate intensity treadmill in hypertensive rats by L-NAME administration did not induce reduction in BP.…”
Section: Renopriva Hypertensionmentioning
confidence: 78%
“…(65,66) Studies from our group showed that 10 weeks of APT mildmoderate intensity treadmill in hypertensive rats by L-NAME administration did not induce reduction in BP. (70) However, an improvement of peripheral insulin sensitivity occurred (69) and reduction of blood pressure levels (unpublished data) after a training session in the L-NAME trained animals compared to the sedentary group.…”
Section: Renopriva Hypertensionmentioning
confidence: 93%